Gestión pública - operativa y su incidencia en la satisfacción de los usuarios del registro municipal de la propiedad del cantón Quevedo, periodo 2013- 2014, modelo de gestión pública-operativa. - Recalde Pacheco, Mónica cristina (2015)
Private management of public administration the Municipal Property Registry Quevedo Canton started its activities as most records nationwide, with inadequate care system to users who come daily to get the services they provide. Currently the Municipal Property Registry Quevedo Canton, has implemented technological tools, refine lacking in institutional management to provide greater customer satisfaction; despite the reduction in service delivery times of 15 days to 3 days, with the average standard 7 working days nationwide. So, this study has the general objective of evaluating the impact of publicoperative management in meeting users Municipal Property Registry of Quevedo. For this, comprehensively analyzed the size of the organization and technical social, cultural, political, control and improvement of the Municipal Property Registry Quevedo Canton areas, adopting based on continuous improvement of services where citizens approach assess the effectiveness of the entity. Therefore, this contribution is intended to contribute to the expectations of users both internal and external, to implement a management model that identifies the differentiating levels of public-operational management for the interaction of the activities to be developed, in order to achieve optimal performance of staff of the institution and satisfy the general interests of society.